Social mobilization and women's participation in water resource management: a case study of Southern Punjab, Pakistan - Hamid, Abdul (2004)
The management of water resources is being challenging day-by-day due to the growing demand of water. Therefore, attention has been diverted towards better management of resources and the role of community. The issue has become more severe for the developing countries, especially in the brackish water zone, the southern Punjab of Pakistan is one of such areas, where people rely completely on surface water for multiple purposes (irrigation, domestic and livestock uses). The reliance of the community on limited water resources for various purposes increases as well as the extensive demand and competition for getting access to and control over water resources. As the rural communities have been divided into different sects based on class, caste and gender, the powerful and influential people get more benefits of the resources, while the women and poor people in general are marginalized. Considering this situation, International Water Management Institute (IWMI) has worked to enhance the role of community, especially the women, since they are using and managing water, particularly for domestic purposes and livestock. The objective was to manage water by maximizing the active participation of women at all levels after assessing their needs and roles to solve water problems locally and effectively. Nevertheless, lack of experience among the community for organizing collective actions was found as a major constraint for the resource management. Earlier efforts in Pakistan towards collective actions in cooperatives had resulted from complete to partial failure. The reason for this has been that only powerful and influential people dominated the organization and that the poor and medium farmers were not represented. The main cause of failure was the badly organized social mobilization process. At the same time, women were kept out of all such participatory projects. The main reasons found by IWMI and Gender Poverty and Water (GP&W) team were their restricted mobility, concept of Purdah (veiling), and dependency on male decisions that made it hard to establish women's organization for water resource management. Therefore, a well-structured social mobilization methodology was adopted to create the awareness among the community members for their involvement in the resource management. The significance and relevance of community's participation for resource management and needs of women's role and contributions is the mainstay of this paper. The village 54/4R in the command area of Hakra 4R distributary in the southern Punjab Pakistan was taken as a case study to analyze whether a well-structured social mobilization approach can help the village community to set up a women organization. Women were organized with the help of male organization at this additional settlement and males played their role as allies of women. The analysis shows that carefully selected leaders representing all social groups in the community, promotion of collective thinking for resource management, awareness raising for women's entities as human beings and capacity building training for both females and males build confidence of the community, particularly of women to understand, communicate and solve their problems. Similarly the community's positive changes in attitude towards female members not only break barriers of restricted mobility and communication, but also help in raising women's voice in resource management related activities.